Changes in women's dietary diversity before and during pregnancy in Southern Benin. Issue 2 (12th December 2019) - Djossinou, Diane R. A.; Savy, Mathilde; Fanou‐Fogny, Nadia; Landais, Edwige; Accrombessi, Manfred; Briand, Valérie; Yovo, Emmanuel; Hounhouigan, D. Joseph; Gartner, Agnès; Martin‐Prevel, Yves
Abstract: Dietary diversity before and during pregnancy is crucial to ensure optimal foetal health and development. We carried out a cohort study of women of reproductive age living in the Sô‐Ava and Abomey‐Calavi districts (Southern Benin) to investigate women's changes in dietary diversity and identify their determinants both before and during pregnancy. Nonpregnant women were enrolled ( n = 1214) and followed up monthly until they became pregnant ( n = 316), then every 3 months during pregnancy. One 24‐hr dietary recall was administered before conception and during each trimester of pregnancy. Women's dietary diversity scores (WDDS) were computed, defined as the number of food groups out of a list of 10 consumed by the women during the past 24 hr. The analysis included 234 women who had complete data. Mixed‐effects linear regression models were used to examine changes in the WDDS over the entire follow‐up, while controlling for the season, subdistrict, socio‐demographic, and economic factors. At preconception, the mean WDDS was low (4.3 ± 1.1 food groups), and the diet was mainly composed of cereals, oils, vegetables, and fish. The mean WDDS did not change during pregnancy and was equally low at all trimesters. Parity and household wealth index were positively associated with the WDDS before and during pregnancy in the multivariate analysis. Additional research is needed to better understand perceptions of food consumption among populations, and more importantly, efforts must be made to encourage women and communities in Benin to improve the diversity of their diets before and during pregnancy.